Networked Closed-Loop Model for Smart On-Site Maintenance of Substation Equipment Using Mobile Networks - Zhenxin Feng; Yi Jiang; Yuting Luo; Kun Zhao; Guocheng Ding; Wenshan Hu (Journal of Control Science and Engineering)
This paper introduces a networked closed-loop model for smart on-site maintenance of substation equipment using mobile networks, which is composed of a field-side Smart Operation and Maintenance (SOM) box with its related APP and a centre-side system platform for Operation and Maintenance (OM). As a bridge to connect the operation sites and data centre, the networked equipment maintenance model enables bidirectional communication among the management, maintenance teams, and diversely located equipment. This model not only realizes the formal data uploading in real-time, but also can provide the workers on site with guidance from the data centre.